Good girls. Season four [videorecording (DVD)]. - Hendricks, Christina, 1975-; Retta; Whitman, Mae, 1988-; Montana, Manny (Universal Pictures Home Entertainment, 2022)
When three suburban moms get tired of trying to make ends meet, they decide it's time to stick up for themselves by robbing the local grocery store. This comedy-infused drama that mixes a little "Thelma & Louise" with a bit of "Breaking Bad". Beth, Ruby, and Annie are knee-deep in a life of crime and there's no going back! This series is packed with twists and surprises, the ladies are taking control of their illegal business operations as they struggle to keep it all hidden and evade those desperate to take them down. Expect steamy romances, nail-biting drama and even higher stakes as the Good Girls have fully broken bad. Season four.